The Issues of Contract in Islamic Stock Transactions on the Indonesia Stock Exchange: A Critical Analysis Based on Maqāṣid al-Sharī‘ah - Hilmi Hadad Alwi; Anton Athoilah (Postgraduate of Univeritas Islam Negeri Sunan Gunung Djati Bandung, 2025)
This study analyzes the issues of contracts in Islamic stock transactions on the Indonesia Stock Exchange (IDX) through a critical analysis based on Maqāṣid al-Sharī‘ah. Islamic stocks, developed to meet the investment needs of Muslim investors, often adopt conventional capital market mechanisms without a deep reconstruction of the fundamental contracts (uqūd). The research identifies issues such as unclear contract structures, ambiguous ownership status, and the potential presence of gharar (excessive uncertainty), maysir (speculation), and ribā (interest) in secondary market transactions. Using a qualitative descriptive-analytical method, this study analyzes fatwas, regulations, and relevant literature in Islamic jurisprudence, as well as Islamic legal objectives. The findings indicate that most sharia-compliant stock transactions do not fully reflect the values of Maqāṣid al-Sharī‘ah, particularly in protecting wealth (ḥifẓ al-māl), ensuring justice, and promoting true public interest (maṣlaḥah). Therefore, a paradigm shift is needed through the reconstruction of contracts based on Maqāṣid, such as proposing a hybrid model that combines musyārakah (partnership) and istikhlāf (trustee). In addition, improving financial literacy and understanding of Islamic contract principles among Muslim investors is crucial to establishing a capital market system that is not only legally compliant but also substantively fair and beneficial.